Determinant physiological factors of simulated BMX race - Daneshfar, A.; Petersen, C.; Gahreman, D. (European Journal of Sport Science, 2021)
Evaluating the physiological demands of BMX cycling on a track provides coaches with the information required to prescribe more effective training programs. To determine the relative importance of physiological factors during simulated BMX race, 12 male riders (age 19.2 ± 3.5 years, height 1.76 ± 0.06 m, mass 68.5 ± 4.3 kg) completed a maximum aerobic capacity (VO2max) test in a laboratory, and a week later, completed six laps on a BMX track interspersed by 15 minutes passive recovery. Peak power, immediate post-lap VO2peak, blood lactate, and heart rate were measured in each lap. Peak power to weight ratio was significantly correlated with lap time, however, the strength of this association decreased in each subsequent lap. Mean VO2peak was greater than 80% of laboratory-measured VO2max in every lap, indicating a strong contribution of the aerobic energy system during BMX racing. This study also identified that mean blood lactate was significantly associated with lap time, which showed the importance of the anaerobic energy system contribution to BMX race. Despite the short period of pedalling during BMX racing, both aerobic and anaerobic energy systems are important contributors to lap performance. Coaches should consider maximizing both anaerobic power and aerobic capacity to improve riders` overall performance in multiple laps.